Genomic Characteristics and Potential Metabolic Adaptations of Hadal Trench Roseobacter and Alteromonas Bacteria Based on Single-Cell Genomics Analyses - Chen, Mingming; Song, Yu; Feng, Xiaoyuan; Tang, Kai; Jiao, Nianzhi; Tian, Jiwei; Zhang, Yao (Frontiers in Microbiology, 2020)
Heterotrophic bacteria such as those from the Roseobacter clade and genus Alteromonas dominate the hadal zones of oceans; however, we know little about the genomic characteristics and potential metabolic adaptations of hadal trench-dwelling bacteria. Here, we report multiple single amplified genomes (SAGs) belonging to Roseobacter and Alteromonas, recovered from the hadal zone of the Mariana Trench. While phylogenetic analyses show that these hadal SAGs cluster with their surface relatives, an analysis of genomic recruitment indicates that they have higher relative abundances in the hadal zone of the Mariana Trench. Comparative genomic analyses between the hadal SAGs and reference genomes of closely related shallow-water relatives indicate that genes involved in the mobilome (prophages and transposons) are overrepresented among the unique genes of the hadal Roseobacter and Alteromonas SAGs; the functional proteins encoded by this category of genes also shows higher amino acid sequence variation than those encoded by other gene sets within the Roseobacter SAGs. We also found that genes involved in cell wall/membrane/envelope biogenesis, transcriptional regulation, and metal transport may be important for the adaptation of hadal Roseobacter and Alteromonas lineages. These results imply that the modification of cell surface-related proteins and transporters is the major direction of genomic evolution in Roseobacter and Alteromonas bacteria adapting to the hadal environment, and that prophages and transposons may be the key factors driving this process.